Factores de riesgo cardiovascular en mujeres obesas menopáusicas y premenopáusicas de Lima Metropolitana - Garmendia, Fausto (2019)
Objective: To determine the frequency of cardiovascular risk factors (CVRF) in obese menopausal and premenopausal women aged 30 to 75 from Metropolitan Lima, Peru. Methods: We conducted a descriptive, analytical, transversal study in 95 obese women aged 30 to 75 from Metropolitan Lima from 2015 to 2017, where 48 were menopausal (MENO) and 47, premenopausal (PREMENO). Obesity grade was determined using the World Health Organization criteria. Conventional methods were used for anthropometry, blood pressure (BP), fasting blood glucose (G), total cholesterol (TC), triglycerides, HDL cholesterol, insulin (I) and transaminases values; VLDL, LDL and non-HDL (cNoHDL), and HOMA coefficient were calculated. We used the program SPSS v. 23 for statistical analysis. We considered obesity, dyslipoproteinemia, high blood pressure, insulin resistance and high transaminases values as CVRF. Results: From a total of 95 obese women, 45.3% had grade I obesity, 28.4% had grade II, and 26.3% had grade III. Compared to premenopausal women, menopausal women were older and had a greater height and higher BP, cNoHDL, insulin and HOMA values. Conclusion: Obese menopausal women presented a higher cardiovascular risk than obese premenopausal women.